Membrane operations innovative separations and transformations - Drioli, E.; Giorno, Lidietta (Weinheim, Germany Wiley‐VCH, 2009)
"The only book dedicated to membrane technology, covering all the different innovative membrane areas from separation to contactors, and regarding them as unit operations in process engineering. The specific potential of these advanced new operations is analyzed by different experts in the field, with regard to their basic aspects and in particular to their potential application for a sustainable growth and improvement in the quality of life. To this end, much emphasis is placed on the role of membrane engineering as a dominant technology in such areas as water desalination or artificial organs. The editors are well known and recognized within the community, while the active experience of the authors provides a highly practical, industrially relevant approach to the subject. Topics considered in detail include membranes in fuel cells, membranes in MEMS and OLEDS, as well as integrated membrane systems"
Includes bibliographical references and index.
Keywords: Membrane separation; Membrane technology; Separation (Technology)